2012
DOI: 10.5194/esd-3-33-2012
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling climate change scenarios for apple pest and disease modeling in Switzerland

Abstract: As a consequence of current and projected climate change in temperate regions of Europe, agricultural pests and diseases are expected to occur more frequently and possibly to extend to previously non-affected regions. Given their economic and ecological relevance, detailed forecasting tools for various pests and diseases have been developed, which model their phenology, depending on actual weather conditions, and suggest management decisions on that basis. Assessing the future risk of pest-related damages requ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…The increase in temperature does not significantly affect the number of applications against both diseases considered (Figure 4). These findings corroborate those reported by Hirschi et al (2012) for fire blight.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in temperature does not significantly affect the number of applications against both diseases considered (Figure 4). These findings corroborate those reported by Hirschi et al (2012) for fire blight.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have suggested that the number of generations of codling moth per year could further Acc e p ted P r e p r i nt increase in the future (e.g., Luedeling et al 2011;Hirschi et al 2012;Juszczak et al 2013). Plum curculio is one of the most important pests for pome and stone fruits in eastern North America (Chouinard 2014b;Hock et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamical models for downscaling are as follows: HadCM3, RegCM, CRCM, RSM, MM5, and WRF [28]. Statistical downscaling could be done with a weather generator (WG), and many WG have been proposed based on the Markov-chain model [27].…”
Section: Climate Change Scenarios and Downscalingmentioning
confidence: 99%
“…The objective of downscaling is to adapt the results obtained from large-scale models into smaller scales in order to apply these data to impact studies. Statistical models and dynamical models represent the most common approaches for downscaling [27]. Dynamical models for downscaling are as follows: HadCM3, RegCM, CRCM, RSM, MM5, and WRF [28].…”
Section: Climate Change Scenarios and Downscalingmentioning
confidence: 99%